Bias Gender Kapamangkuan Di Desa Mengesta Kecamatan Penebel Kabupaten Tabanan - I Wayan Wastawa; I Wayan Suwadnyana (Jayapangus Press, 2021)
The analysis of the kapamangkuan gender bias in Mengesta village is a socio-cultural study of the imbalance of rights and obligations between pamangku lanang and pamangku istri. This study uses a qualitative methodology, data collection were done through observations, literature study, and in-depth interviews with 7 traditional and religious leaders as informants. The present study concludes that the procedures for pamangku candidates' coronation were as follows: selection, lineage, nyanjan ceremony, and distribution of lekesan. Gender inequality exists due to several factors, namely: the purusa and pradana system in Balinese culture; 2) male dominance in kapamangkuan; 3) kapamangkuan education prioritizes pamangku lanang; 4) The labeling of pamangku istri with their domestic duties as ceremonial amenities maker, and 5) menstrual cycle myths factors. Furthermore, the gender identification in kapamangkuan in Mengesta village are as follows: 1) The labeling of pamangku istri as the socialization of women into gender polarity; 2) the kapamangkuan education system based on biological differentiation, 3) a second marriage system that is considered unholy, 4) through unclear patterns of pamangku istri's clothing, and 5) Gender identification through adat (local social system). In general, there is still injustice to pamangku istri regarding her rights and obligations despite her equal position as a pamangku.